Fate and potential risks of microplastic fibers and fragments in water and wastewater treatment processes - Na, Sang-Heon; Kim, Min Ji; Kim, Jihee; Batool, Rida; Cho, Kyungjin; Chung, Jaeshik; Lee, Seung hak; Kim, Eun Ju (Elsevier BV, 2024)
Water and wastewater treatment plants (WWTPs) receive various types of microplastics (MPs), with fibers and fragments being dominant shapes. Here we investigated the removal behavior and transformation of MPs (polypropylene and polyethylene terephthalate fibers and fragments) in simulated water and wastewater treatment units, including activated sludge process, coagulation, sand filtration, and advanced oxidation/disinfection. Sand filtration demonstrated the highest average efficiency in removing MPs (98 %), followed by activated sludge process (61 %) and coagulation (55 %), which was associated with their physicochemical properties (shape, size, density, surface functional groups, etc). In activated sludge process and coagulation, the polymer type had a greater impact on the removal of MPs than the particle shape, while in sand filtration, the particle shape played a more important role. When subjected to the long-term operation and backwashing of sand filters, approximately 15 % of the initially filtered fragments broke through the sand media, with nearly no fibers escaping. UV-based advanced oxidation and chlorination induced the leaching of dissolved organic matters with different molecular characteristics from fragment MPs, resulting in varying levels of cytotoxicity and bacterial toxicity. Our study provides important information for predicting the fate of MPs and mitigating their impacts in WWTPs.